Harmonization of Soil Functions in Maintaining Food Security according to Agrarian Jurisprudence - Nada Nabila Fatihah; M. Junaidi (Universitas Muhammadiyah Surakarta, 2025)
The writing of this article is with the aim of analyzing the harmonization of soil functions in maintaining food security according to agrarian jurisprudence. This research was taken based on problems that arise in large-scale land use, which tends to be in the development sector to meet personal needs, as well as declining land use for food needs. Food security is a vital need that must be met and maintained for survival. In this writing, it is based on library research using the normative juridical approach method, which is an approach based on normative postulates in the Qur'an and hadith as well as the rules of fiqh. This research raises the perspective of agrarian jurisprudence as a basis for analyzing and solving food security problems, which integrates Islamic principles with the importance of soil function management. The results of the study show that maintaining soil harmonization is very important to maintain food availability. In addition, this study found that in agrarian jurisprudence, sustainable land management, fair distribution, and prohibition of exploitation can strengthen food security. The conclusion of this study is that the application of agrarian fiqh principles can provide solutions in maintaining soil function and food security challenges. The implementation of fair and sustainable agrarian policies is needed to achieve the welfare of the entire community. As well as increasing awareness of the importance of harmonizing soil functions in maintaining food security.